Bridging the Gap Between Evidence and Argument: Exploring Undergraduate EFL Students’ Struggles with Logical Warrants in Academic Writing - Muthmainnah Mursidin; Ida Ilmiah Mursidin (Universitas Muria Kudus, 2026)
The ability to integrate facts and opinions through logical warrants constitutes a fundamental yet frequently neglected competency in undergraduate academic writing. This study investigates the nature and causes of undergraduate EFL students' struggles with logical warrant construction and examines how these difficulties impede broader critical thinking development. Employing a descriptive qualitative design, data were collected from 20 undergraduate students enrolled at Universitas Islam Makassar, South Sulawesi, Indonesia, through three instruments: a Critical Thinking-Based Writing Test, a short essay assignment, and a focused interview protocol. Findings were analyzed using Toulmin's Argumentation Model (2021), focusing on the presence and quality of Claims, Data, and Warrants. The results reveal a profound